Traumatic Brain Injury in Children: Glial fibrillary Acidic Protein and Clinical Outcomes. Issue 3 (1st March 2022) - Ryan, Emer; Kelly, Lynne; Stacey, Catherine; Duff, Eimear; Huggard, Dean; Leonard, Ann; Boran, Gerard; McCollum, Danielle; Doherty, Dermot; Bolger, Turlough; Molloy, Eleanor J.
Abstract : Objectives: Glial fibrillary acidic protein (GFAP) is a neuronal protein released after traumatic brain injury (TBI) and detectable in serum samples. GFAP correlates with symptom severity in adults and may be a marker of brain injury in children with milder symptoms or preverbal children. Methods: GFAP was examined in children with severe TBI (initial Glasgow Coma Scale score <8), with mild TBI (Glasgow Coma Scale score 14/15), and at 0 to 4 and at 10 to 14 days after TBI and was compared with healthy age-matched controls. Mechanism, time points from injury, and symptoms were recorded. Results: The study enrolled 208 children including 110 with TBI (n = 104 mild, 6 severe) and controls (n = 98). GFAP was higher in mild TBI than in controls and highest in the severe TBI cohort, with a maximum value at 6 hours from injury. Vomiting was significantly associated with higher GFAP levels, but no association was found with amnesia, loss of consciousness, and the Sports Concussion Assessment Tool. Children reporting >1-point changes from their preinjury functioning on the Post-Concussive Symptom Inventory had higher initial GFAP but not total Post-Concussive Symptom Inventory score changes. Conclusions: GFAP identifies children with TBI, even at the milder end of the spectrum, and is strongly associated with postinjury vomiting. It may be a useful marker of pediatric TBI; however, sampling is time critical.